2021
DOI: 10.3390/w13081013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Shifts in Historic and Future Temperature and Precipitation Patterns Related to Snow Accumulation and Melt Regimes in Alberta, Canada

Abstract: Shifts in winter temperature and precipitation patterns can profoundly affect snow accumulation and melt regimes. These shifts have varying impacts on local to large-scale hydro-ecological systems and freshwater distribution, especially in cold regions with high hydroclimatic heterogeneity. We evaluate winter climate changes in the six ecozones (Mountains, Foothills, Prairie, Parkland, Boreal, and Taiga) in Alberta, Canada, and identify regions of elevated susceptibility to change. Evaluation of historic trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 88 publications
4
19
0
Order By: Relevance
“…In addition, we observed significant cooling trends in the month of November (see Figure 3e,j) that coincided with other studies reported for the same area for the latter half of the last century [69,70]. Such cooling trends could be associated with the decrease in winter precipitation (including November) in Alberta [71], where less precipitation would potentially cause cooler winter temperatures in some places in Canada [72]. Overall, we found declining LST in the late spring and winter (especially October, November, and February) in most of the subregions; however, those were not significant (see Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we observed significant cooling trends in the month of November (see Figure 3e,j) that coincided with other studies reported for the same area for the latter half of the last century [69,70]. Such cooling trends could be associated with the decrease in winter precipitation (including November) in Alberta [71], where less precipitation would potentially cause cooler winter temperatures in some places in Canada [72]. Overall, we found declining LST in the late spring and winter (especially October, November, and February) in most of the subregions; however, those were not significant (see Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 91%
“…In mid‐high latitude regions, snowpack dynamics also exert a key control on seasonal streamflow discharge distributions. Over the last two decades, it has been well documented that warming has advanced snowmelt timing by decreasing snowpack depth and increasing winter rainfall in both western and eastern North America (Dudley et al, 2017; Ford et al, 2021; Harpold et al, 2012; Hodgkins & Dudley, 2006; Huntington et al, 2004; Mote et al, 2005; Newton et al, 2021). Shallower snowpack and earlier snowmelt may lead to implications for the magnitude and timing of spring streamflow, as well as water availability during summer (Barnett et al, 2005; Creed et al, 2015; Suzuki et al, 2020; Xu et al, 2009; Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the climatological changes in the water balance of this region at three periods in the future. We examined future and historical simulations from the Coupled Model Intercomparison Project (CMIP) Phase 6 [11], and specifically 25 ensemble members (r1i1p1f1 to r25i1p1f1) of the Canadian Earth System Model version 5 (CanESM5) [12]. The ensemble members have the same physics and same forcings but different initial conditions.…”
Section: Methodsmentioning
confidence: 99%